Summer changes in cyanobacterial bloom composition and microcystin concentration in eutrophic Czech reservoirs - Znachor, Petr; Jurczak, Tomasz; Komárková, Jaroslava; Jezberová, Jitka; Mankiewicz, Joanna; Kastovská, Klára; Zapomelová, Eliska (Environmental toxicology, 2006)
In mid-July and August 2003 and 2004, 18 reservoirs in the Czech Republic were sampled for phytoplankton species composition and concentration of intracellular microcystins (MCs). As a consequence of high nutrient loading, most of the reservoirs experienced cyanobacterial blooms of various intensities, with the prevalence of cyanobacteria increasing markedly in August, along with a conspicuous shift in species composition toward dominance of Microcystis spp. Microcystins were detected in 90% of the samples, and their amount also increased considerably in August, reflecting the cyanobacterial biomass. In Microcystis-dominated samples, a significantly higher amount of MCs (p < 0.001) occurred than in samples in which other taxa prevailed. Microcystins were positively correlated with chlorophyll a and cyanobacterial biovolume (p < 0.05, R2 = 0.61 and 0.66, respectively), with the strongest correlation found for Microcystis spp. biovolume (p < 0.001, R2 = 0.87). This taxon was the most important producer of MCs in Czech reservoirs. The main structural variants of MCs were MC-LR, MC-RR, and MC-YR. This study's data also indicate that the relative share of MC variants (MC-LR and MC-RR) varies considerably with time, most likely as a consequence of different species and strain compositions during the summer. This study clearly demonstrates a high prevalence of MC-producing cyanobacteria in Czech reservoirs. Therefore, regular monitoring of these reservoirs is highly desirable in an effort to minimize potential health risks to the human population.
Keywords: mikrocystiny; Cyanobacteria; Population Dynamics; Seasons; sinice; Biomass; monitorování životního prostředí; Microcystins; roční období; zásobování vodou; Fresh Water; Eutrophication; cyklické peptidy; sladká voda; Czech Republic; Environmental Monitoring; populační dynamika; eutrofizace; Peptides, Cyclic; Česká republika; Water Microbiology; Water Supply; mikrobiologie vody; biomasa